2022
DOI: 10.1002/jper.21-0595
|View full text |Cite
|
Sign up to set email alerts
|

Association of peptidoglycan recognition protein 1 to post‐myocardial infarction and periodontal inflammation: A subgroup report from the PAROKRANK (Periodontal Disease and the Relation to Myocardial Infarction) study

Abstract: Background: Peptidoglycan recognition protein 1 (PGLYRP1) is an antimicrobial and proinflammatory innate immunity protein activated during infections. We aimed to investigate whether PGYLRP1 and associated molecules of the immune response in saliva is a cumulative outcome result of both MI and periodontal inflammation. Methods and Results:Two hundred patients with MI and another 200 matched non-MI controls were included. A full-mouthexamination was conducted to assess periodontal inflammation and collection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
2
5
0
Order By: Relevance
“…For example, absence of bleeding is a reliable predictor of periodontal stability, and over 60% of the sites that lost attachment during a follow-up of over 50 months were in patients with mean BOP ≥ 30% (Joss et al, 1994;Lang et al, 1990). Of note, gingival bleeding is a determinant of the levels of both markers in saliva, which has also been shown in a previous study (Rathnayake et al, 2022).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…For example, absence of bleeding is a reliable predictor of periodontal stability, and over 60% of the sites that lost attachment during a follow-up of over 50 months were in patients with mean BOP ≥ 30% (Joss et al, 1994;Lang et al, 1990). Of note, gingival bleeding is a determinant of the levels of both markers in saliva, which has also been shown in a previous study (Rathnayake et al, 2022).…”
Section: Discussionsupporting
confidence: 75%
“…TREM‐1 saliva levels were also elevated in both children with cystic fibrosis and systematically healthy children in the presence of gingivitis compared to periodontal health (Yucel et al, 2020). Furthermore, a positive correlation was reported between TREM‐1 serum and saliva levels in patients with periodontitis (Bostanci, Oztürk, et al, 2013), as well as between TREM‐1 and PGLYRP1 levels both in serum and saliva (Bostanci, Oztürk, et al, 2013; Inanc et al, 2021; Rathnayake et al, 2022; Silbereisen et al, 2019; Yucel et al, 2020). Aside from this, collection of saliva, compared to blood, is simple, cheap and non‐invasive (Giannobile, 2012; Taylor & Preshaw, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Increasing plaque mass was found to be associated with higher PGLYRP1 levels in saliva. [12][13][14] Besides the bacterial challenge, evidence suggests the presence of other factors that interfere with TREM-1 function or expression. Clinical studies reported relationship between elevated TREM-1 serum levels and noninfectious inflammatory diseases such as rheumatoid arthritis, 15,16 and Behçet's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Peptidoglycan recognition protein 1 (PGLYRP1), the functional ligand of TREM‐1, is being secreted upon bacterial challenge 11 . Increasing plaque mass was found to be associated with higher PGLYRP1 levels in saliva 12–14 . Besides the bacterial challenge, evidence suggests the presence of other factors that interfere with TREM‐1 function or expression.…”
Section: Introductionmentioning
confidence: 99%